2004
DOI: 10.1007/s00442-004-1770-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and social effects on reproduction and local recruitment in the red-backed shrike

Abstract: Numerous hypotheses have been proposed to explain variation in reproductive performance and local recruitment of animals. While most studies have examined the influence of one or a few social and ecological factors on fitness traits, comprehensive analyses jointly testing the relative importance of each of many factors are rare. We investigated how a multitude of environmental and social conditions simultaneously affected reproductive performance and local recruitment of the red-backed shrike Lanius collurio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(108 citation statements)
references
References 40 publications
8
84
0
2
Order By: Relevance
“…In our study population, nesting success was found to decrease with increasing conspecific density in the neighborhood of a territory (Müller et al 2005). We therefore predicted that probability of breeding dispersal is positively related to conspecific density around a territory (prediction 3a, Table 1).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In our study population, nesting success was found to decrease with increasing conspecific density in the neighborhood of a territory (Müller et al 2005). We therefore predicted that probability of breeding dispersal is positively related to conspecific density around a territory (prediction 3a, Table 1).…”
Section: Introductionmentioning
confidence: 89%
“…In our study population, territory quality has been shown to influence local recruitment, with probability of recruitment increasing with territory quality (Müller et al 2005). If site choice is important for dispersal, we therefore expect probability of breeding dispersal to be negatively related to quality of the territories held in the year before dispersal (prediction 2a, Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Επιπλέον, βρέθηκε ότι οι κτηνοτροφικές εγκαταστάσεις και τα γεωργικά κτίρια δεν επηρεάζουν τον πλούτο των πουλιών προτεραιότητας. Όσον αφορά στα είδη Lanius, αυτό μπορεί να οφείλεται εν μέρει στην οικολογία τους, γιατί προτιμούν ως ενδιαιτήματα αναπαραγωγής εκείνα που παρέχουν επαρκή κάλυψη για τις φωλιές τους (Muller et al 2005), ενώ χρειάζονται και περιοχές με διάσπαρτα δέντρα, θάμνους και φυτοφράκτες καθώς αυτές παρέχουν περισσότερες θέσεις εποπτείας και συμβάλλουν στην επιτυχή σύλληψη της λείας (Brambilla et al 2007 …”
Section: μέγεθος οικισμώνunclassified